2020
DOI: 10.1021/acs.jafc.9b08033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dazomet Fumigation on Soil Phosphorus and the Composition of phoD-Harboring Microbial Communities

Abstract: The soil phosphorus (P) cycle and P transformation are largely driven by the soil bacterial microbial community. However, little is known about the effects of dazomet (DZ) soil fumigation on soil P and soil microbial communities associated with P transformation. This research investigated P released from three farm soils as a result of DZ fumigation and changes in enzyme activity, gene abundance, and the encoding alkaline phosphatase PhoD microbial community. After DZ fumigation, we observed a briefly signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
2
17
1
Order By: Relevance
“…More specifically, the class Actinobacteria was dominant in E (47.45%) while Alphaproteobacteria reduced from 15.29 to 4.84 % and minimum in E. The abundance of Ktedonobacteria and Gammaproteobacteria were increased (6.09-1.09% and 5.11-12.32%) as well as richest in D treated soil, and the richest genus of Arthrobacter and Bacillus were highest in E (19.74% and 4.45%) (Figure1). Similarly, Huang et al[23] observed significantly increased in Arthrobacter abundance in dazomet treated soil, which might be attributed by Arthrobacter ability to degrade dazomet as a nutrient source.…”
mentioning
confidence: 79%
“…More specifically, the class Actinobacteria was dominant in E (47.45%) while Alphaproteobacteria reduced from 15.29 to 4.84 % and minimum in E. The abundance of Ktedonobacteria and Gammaproteobacteria were increased (6.09-1.09% and 5.11-12.32%) as well as richest in D treated soil, and the richest genus of Arthrobacter and Bacillus were highest in E (19.74% and 4.45%) (Figure1). Similarly, Huang et al[23] observed significantly increased in Arthrobacter abundance in dazomet treated soil, which might be attributed by Arthrobacter ability to degrade dazomet as a nutrient source.…”
mentioning
confidence: 79%
“…In particular, the soil bacterial community structure significantly changed after DZ and CP fumigation. In many studies, DZ fumigation significantly altered the bacterial abundance as well as the abundance, diversity, and composition of the overall microbial community [53,54]. The results showed that Firmicutes were the predominant phylum, accounting for 47.4% of the total bacterial flora.…”
Section: Effects Of Different Disinfection Methods On Bacterial Compositionmentioning
confidence: 99%
“…When fumigants (DMDS, chloropicrin, 1,3-D) were used alone, a higher dosage was required for V. dahliae and Meloidogyne incognita suppression, but when any two of these fumigants were combined, the lower dosage was effective [144]. Dazomet was also reported to promote phosphorus mineralization and allowed crops to absorb and use phosphorus [145].…”
Section: Chemicals In Use For Verticillium Wilt Managementmentioning
confidence: 99%